2022
DOI: 10.1007/jhep06(2022)150
|View full text |Cite
|
Sign up to set email alerts
|

Quasinormal modes for massive charged scalar fields in Reissner-Nordström dS black holes: anomalous decay rate

Abstract: The anomalous decay rate of the quasinormal modes occurs when the longest-lived modes are the ones with higher angular number. Such behaviour has been recently studied in different static spacetimes, for uncharged scalar and fermionic perturbations, being observed in both cases. In this work we consider the propagation of charged massive scalar fields in the background of Reissner-Nordström-de Sitter black holes and we mainly study the effect of the scalar field charge in the spectrum of quasinormal frequencie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Introducing another scale in the theory through the presence of a cosmological constant an anomalous behavior of QNMs was found in [44] as the result of the interplay of the mass of the scalar field and the value of the cosmological constant. Anomalous QNMs decay modes were also found if the background metric is the Reissner-Nordström and the probe scalar field is massless [45] of massive [46] depending on critical values of the charge of the black hole, the charge of the scalar field and its mass. The decay modes of QNMs in various setups were studied in [47][48][49][50].…”
Section: Introductionmentioning
confidence: 95%
“…Introducing another scale in the theory through the presence of a cosmological constant an anomalous behavior of QNMs was found in [44] as the result of the interplay of the mass of the scalar field and the value of the cosmological constant. Anomalous QNMs decay modes were also found if the background metric is the Reissner-Nordström and the probe scalar field is massless [45] of massive [46] depending on critical values of the charge of the black hole, the charge of the scalar field and its mass. The decay modes of QNMs in various setups were studied in [47][48][49][50].…”
Section: Introductionmentioning
confidence: 95%
“…These decay patterns are associated with modes of the pure de Sitter space deformed by a black hole [14,15]. Quasinormal modes of such massive fields in Schwarzschildde Sitter and Reissner-Nordström backgrounds have been extensively studied, as evidenced by works such as [16][17][18][19][20], with particular attention paid to the anomalous decay rate in the regime μM/m 2 P 1 [21,22] and Strong Cosmic Censorship [23,24]. Mathematical aspects of asymptotic decay around black holes embedded in de Sitter space were addressed in [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…For horizonless compact objects, there could be echoes in the ringdown signal, which is the smoking gun for the existence of the horizonless compact objects [15,22,36]. One can also use the QNMs to constrain modified gravity theories [37][38][39][40][41][42][43][44][45]. It has also been found that the QNM spectrum is unstable under a small perturbation of the potential [46,47].…”
Section: Introductionmentioning
confidence: 99%